A Discussion on the Text Known as "The Sutra of Fire Blessing" by Mergen Gegeen Luvsandambijantsan - Wuyun (Tibetan Studies, 2025)
This article takes as its primary source the work entitled "The Sutra of Fire Blessing," which is found within the four-volume woodblock-printed collection from 1783 known as "The Decree of Vajradhara Mergen Da Yanchi Lama's Enlightenment," by Urad's Mergen Gegeen Luvsandambijaltsan. The study conducts a comparative analysis of manuscript and print versions to trace the characteristics of their transmission and variation. Furthermore, it provides a detailed analysis of the content, ideological meaning, and stylistic features of Mergen Gegeen's "Sutra of Fire." Мэргэн гэгээн Лувсандамбийжалцаны “Галын ерөөлийн судар хэмээгдэх оршив” зохиолын тухайд өгүүлэх нь Хураангуй: Тус өгүүлэлд Урадын Мэргэн гэгээн Лувсандамбийжалцаны 1783 онд модон бараар хэвлэгдсэн "Очир дара мэргэн даяанч ламын гэгээний бум зарлиг хэмээгдэх оршвой" гэх дөрвөн боть сүмбүмд байгаа “Галын ерөөлийн судар хэмээгдэх оршвой" зохиолоор үндсэн эх болгон, бичмэл дармал хэвлэлүүдийг харьцуулан улирч хувирсан онцлог, Мэргэн гэгээний галын судрын агуулга, утга санаа, туурвил зүйн онцлогийг задлан шинжилсэн болно. Түлхүүр үг: Мэргэн гэгээн, Лувсандамбийжалцан, Галын судар, онцлог